Programmed death-1 and its ligand are novel immunotolerant molecules expressed on leukemic B cells in chronic lymphocytic leukemia. - Maciej Grzywnowicz (Public Library of Science (PLoS), 2012)
Programmed death-1 (PD-1) is an immunoreceptor predominantly expressed on exhausted T cells, which through an interaction with its ligand (PD-L1), controls peripheral tolerance by limiting effector functions of T lymphocytes. qRT-PCR for PD-1, PD-L1 and their splicing forms as well as flow cytometric assessment of surface expression was performed in a cohort of 58 chronic lymphocytic leukemia (CLL) patients. In functional studies, we assessed the influence of the proliferative response of leukemic B-cells induced by IL-4 and CD40L on PD-1 transcripts and expression on the protein level. The median level of PD-1, but not PD-L1, transcripts in CLL patients was higher in comparison to healthy volunteers (HVs, n = 43, p = 0.0057). We confirmed the presence of PD-1 and PD-L1 on the CLL cell surface, and found the expression of PD-1, but not PD-L1, to be higher among CLL patients in comparison to HVs (47.2% vs. 14.8%, p<0.0001). The Kaplan-Meier curves for the time to progression and overall survival in groups with high and low surface expression of PD-1 and PD-L1 revealed no prognostic value in CLL patients. After stimulation with IL-4 and CD40L, protein expression of PD-1 was significantly increased in samples that responded and up-regulated CD38. PD-1, which is aberrantly expressed both at mRNA and cell surface levels in CLL cells might represent a novel immunotolerant molecule involved in the pathomechanism of the disease, and could provide a novel target for future therapies.